Confirmatory report of Damselfly (Odonata) Pixie Dartlet, Ischnura nursei (Morton, 1907) from Bangladesh - Rahaman Naim, Md Hamidur; Shalauddin, Md; Raha Antu, Durjoy (Bangladesh Journal of Zoology, 2023)
Abstract not available Bangladesh J. Zool. 51(1): 129-133, 2023